2016
DOI: 10.1089/brain.2016.0432
|View full text |Cite
|
Sign up to set email alerts
|

Altered Resting-State Functional Connectivity in the Hand Motor Network in Glioma Patients

Abstract: To examine the functional connectivity of the primary and supplementary motor areas (SMA) in glioma patients using resting-state functional MRI (rfMRI). To correlate rfMRI data with tumor characteristics and clinical information to characterize functional reorganization of resting-state networks (RSN) and the limitations of this method. This study was IRB approved and in compliance with Health Insurance Portability and Accountability Act. Informed consent was waived in this retrospective study. We analyzed rfM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 36 publications
3
30
0
Order By: Relevance
“…It has been suggested that altered RS-fMRI functional connectivity in the SM network can occur on the same basis in patients with brain tumors 49 . Although neurovascular uncoupling could be a contributor in the cases that fail our RS-fMRI analysis, our overall failure rate is low, and, in most cases, we can identify a specific cause for this failure, typically, patient motion or sedation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that altered RS-fMRI functional connectivity in the SM network can occur on the same basis in patients with brain tumors 49 . Although neurovascular uncoupling could be a contributor in the cases that fail our RS-fMRI analysis, our overall failure rate is low, and, in most cases, we can identify a specific cause for this failure, typically, patient motion or sedation.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, a few publications (Agarwal et al, 2016a(Agarwal et al, , 2016bMallela et al, 2016) have demonstrated similar impaired BOLD responses in rsfMRI due to brain tumor-induced NVU. Studies by Agarwal et al (2016b) have demonstrated that tumor-related NVU can adversely affect the restingstate BOLD signal similar to its effect on task-based BOLD activation.…”
Section: Introductionmentioning
confidence: 90%
“…Another study demonstrated that brain tumor-related NVU may also similarly affect rsfMRI at ultrahigh field (7 Tesla) despite the higher signal-to-noise ratio afforded by higher field strength (Agarwal et al, 2016a). Mallela et al (2016) have examined the correlation of rsfMRI data with tumor characteristics and clinical information to characterize functional reorganization of resting-state networks (RSNs) and the limitations of this method in high-grade gliomas due to NVU. Thus, practical application of rsfMRI for presurgical planning should take into account the possibility of NVU to ensure mapping accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…51 Because of its easy implementation and less stringent requirements for patient compliance, rsfMRI has been attracting wide attention for use as a preoperative mapping tool. 52,53 However, rsfMRI also suffers from similar important clinical limitations of false negative BOLD signals due to brain-tumor related NVU; 5456 thus, to use rsfMRI as a reliable pre-surgical tool, it becomes all the more important to study NVU in cases of focal resectable brain lesions such as tumors to evaluate its effects on rsfMRI.…”
Section: Head Motion and Physiologic Noisementioning
confidence: 99%
“…56 Mallela and colleagues examined the correlation of rsfMRI data with tumor characteristics and clinical information to characterize functional reorganization of RSNs and the limitations of rsfMRI in high-grade gliomas due to NVU. 54 …”
Section: Head Motion and Physiologic Noisementioning
confidence: 99%